2019
DOI: 10.1109/tcomm.2018.2867490
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Processing Design for Multipair Massive MIMO Relaying With Channel Spatial Correlation

Abstract: Abstract-Massive multiple-input multiple-output (MIMO) avails of simple transceiver design which can tackle many drawbacks of relay systems in terms of complicated signal processing, latency, and noise amplification. However, the cost and circuit complexity of having one radio frequency (RF) chain dedicated to each antenna element are prohibitive in practice. In this paper, we address this critical issue in amplify-andforward (AF) relay systems using a hybrid analog and digital (A/D) transceiver structure. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The differences between the two structures are that the sub-connected structures use less phase shifters than the full-connected structures with the same number of antennas and RF chains, but in performance, the sub-connected structures are slightly lower than the full-connected ones. The hybrid beamforming of relay system with full-connected structure have been designed in [20] and [21], but they are not based on mmWave large-scale antenna arrays. For the AF mmWave massive MIMO relay system with the full-connected structure, the joint optimal hybrid beamforming designs of downlink single-destination and multi-destination using matching pursuit (MP) algorithms have been studied in [22] and [23], respectively, and a separate design scheme of analog and digital beamforming of downlink multi-destination has been studied in [24].…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the two structures are that the sub-connected structures use less phase shifters than the full-connected structures with the same number of antennas and RF chains, but in performance, the sub-connected structures are slightly lower than the full-connected ones. The hybrid beamforming of relay system with full-connected structure have been designed in [20] and [21], but they are not based on mmWave large-scale antenna arrays. For the AF mmWave massive MIMO relay system with the full-connected structure, the joint optimal hybrid beamforming designs of downlink single-destination and multi-destination using matching pursuit (MP) algorithms have been studied in [22] and [23], respectively, and a separate design scheme of analog and digital beamforming of downlink multi-destination has been studied in [24].…”
Section: Introductionmentioning
confidence: 99%
“…A general downside of high-gain antenna systems can be the decreased beamwidth. In [5], it is shown that the reduced beamwidth restricts the angular spread of the received signals, which affects the channel covariance matrix's eigenvalues, resulting in a MIMO performance degradation. Therefore, in [6] it was studied how the decrease of the beamwidth influences the performance of fixed-beam antenna systems, which uses high-gain antenna elements to partition a sector in smaller areas.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, spatial channel correlation is an important property of multiuser MIMO [14]. The propagation channels and antenna arrays create spatial channel correlation, which has a non-negligible impact on the performance of CF massive MIMO [15].…”
Section: Introductionmentioning
confidence: 99%